Ultrastructural Comparison of Processing of Protein and Pigment in the Ink Gland of Four Species of Sea Hares. (24th May 2015) - Prince, Jeffrey S.; Johnson, Paul Micah
Abstract : The ink glands of four sea hare species ( Aplysia californica, A. parvula, A. juliana, and Dolabrifera dolabrifera ) were compared to determine where ink protein is synthesized, how it is incorporated into protein storage vesicles, and the degree of variation in the structure of the ink gland. Ink protein was synthesized in RER cells and stored in amber and white vesicles. Lack of competent RER cells in the ink gland of D. dolabrifera was correlated with the absence of ink protein. Ink protein had similar characteristics in all three Aplysia species but, again, it was absent in D. dolabrifera . Its uptake involved pinocytosis by protein vesicle cell membranes. Granulate cells showed little variation in structure among the four species, the opposite was the case for RER cells. The conversion of the red algal pigment, phycoerythrin, to phycoerythrobilin (PEB) occurs in the digestive gland but the change of PEB to aplysioviolin (APV), the form of pigment released by the ink gland, occurs in the ink gland itself by both granulate cells and pigment vesicles. The literature describes five types of vesicles based upon color and contents in the ink gland of these four species. We report only three types of vesicle: colored (purple), protein (white and amber), and transparent (includes clear vesicles).